Single-crystal silicon/silicon dioxide multilayer heterostructures based on nanomembrane transfer - COLAVITA, PAULA (My University, 2007)
A method to fabricatesingle-crystalSi/SiO2multilayerheterostructures is presented. Heterostructures are fabricated by repeated transfer of single crystalsiliconnanomembranes alternating with deposition of spin-on-glass. Nanomembrane transfer produces multilayers with low surface roughness and smooth interfaces. To demonstrate interface quality, the specular reflectivities of one-, two-, and three-membrane heterostructures are measured. Comparison of the measured reflectivity with theoretical calculations shows good agreement. Nanomembrane stacking allows for the preprocessing of individual membranes with a high thermal budget before the low thermal budget assembly of the stack, suggesting a new avenue for the three dimensional integration of integrated circuits.
PUBLISHED
Keywords: Heterojunctions; Reflectivity